“PENGARUH LIVE STREAMING TIKTOK TERHADAP PENINGKATAN PENJUALAN UMKM KULINER DI ROKAN HULU” - Ervina Ningtias (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of TikTok live streaming on increasing sales of culinary MSMEs. The development of digital technology and social media has driven changes in business marketing strategies, particularly in the MSME sector. TikTok has become a digital platform widely used by businesses due to its ability to reach consumers widely and quickly. The research approach used a qualitative descriptive method. The research subjects consisted of business owners and several consumers. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used an interactive model that included data reduction, data presentation, and drawing conclusions. The results show that live streaming is a primary marketing tool capable of increasing sales through content consistency, creativity, and interaction with consumers. One example is TikTok, which has a positive and significant impact on increasing sales of culinary MSMEs in Rokan Hulu. The better the quality of the content created, the higher the increase in business sales. This research is expected to serve as a reference for MSMEs in utilizing social media, including TikTok, as a digital marketing strategy.